EFL Teacher's Strategies in Online Learning Environment at SMK Nasional Makassar - Setiawati, Nurul Sri; Sunra, La; Sakkir, Geminastiti (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this research is to explore the strategies used by English teachers in implementing learning during online classes. This research is qualitative research with a case study approach through interviews. The participants in this study were 2 English teachers from Makassar National Vocational School. The data in this study were obtained through 3 parts of interviews with a total of ten questions. The findings show that the strategies used by English teachers in implementing learning during online classes are diagnostic assessment and discovery learning using several applications including WhatsApp, Zoom, Google Classroom, YouTube, Google Forms, and the Google search engine. Teachers used several other strategies involving peer tutoring, using school facilities, implementing synchronous online learning, and parental counseling to overcome challenges. Therefore, it is recommended for teachers to continue to use or apply a combination of strategies that they have implemented. In addition, because there are also several strategies discussed in this study, readers of this study, especially teachers, can also use other strategies and technologies to increase the variety of their learning activities. Finally, during the observation of the application of discovery learning, the teacher used it to recount text materials with a combination of writing and speaking projects. It has the potential to be used differently in different material focuses and skills. So, it is also suggested that future researchers be more specific with certain aspects of teaching English such as language skills, or certain materials to enrich data related to that field.